DETERMINASI IKLIM KOMUNIKASI, KOMPETENSI, DAN DISIPLINKERJA TERHADAP KINERJA PEGAWAI KANTOR DISTRIK NAVIGASI KELAS I TANJUNGPINANG, MELALUI KEPUASAN KERJASEBAGAI INTERVENING - Yuritanto Yuritanto (Journal Competency of Business, 2020)
Research this is a research descriptive quantitative about climate communication, competence, discipline to the performance employee through satisfaction work as a variable intervening. Research this for obtain data and information about climate communication, competence, discipline work and satisfaction employee used as ingredients analysis for knowing the effect to the performance District Office staff Navigation Class I Tanjungpinang, chosen as target research or object research. With framework work this, survey data collection is carried out with make use of questionnaire stage attitude that has been done adapted for topics research this total respondent on research this as many as 142 people. For could characterize attitude, structure model with tool measuring help SmartPLS 3.2.8 for made into as framework work researc. Results research to show that has been happen circuited an significant between variable Climate communication , competence , and Discipline to Performance employee as big as 40.3 %, and the rest as big as 59.7 % explained by extract others outside of the research in research this. Majority respondent at the location research has been have insight in respond to research this which is based on influence and benefits (impact) for employee that is. Data results research to show has been meet Composite assumption Reliability with value percentage spread as big as 80.6% for climate communication , 81 % for competence , 79.6% discipline employee and 85.9 % performance employee and 81% for satisfaction work employee . Showing that the indicator on each constructor have consistency reability high.